1992
DOI: 10.1164/ajrccm/145.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Mucus from Asymptomatic Smokers Is Better Hydrated and More Easily Cleared by Mucociliary Action

Abstract: We compared the physical and transport properties of tracheal mucus collected from 16 asymptomatic smokers and from 18 nonsmokers. The smokers produced a larger volume of mucus (wet weight 18.6 versus 11.2 mg; p = 0.04) with a lower solids content (11.5 versus 16.3%; p = 0.02) and a lower modulus of rigidity (log G* 2.37 versus 2.62; p = 0.04). Although the smokers mucus had a 40% faster mucociliary transport rate on the frog palate (p = 0.04), the cough clearability was nearly identical to the mucus from nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 4 publications
1
28
0
4
Order By: Relevance
“…CS is highly oxidizing, which decreases CFTR gene expression, and CS exposure also causes CFTR clearance from the plasma membrane into aggresome-like compartments (14,16). Both of these effects result in a functional decrease in CFTR activity in the plasma membrane, which reduces salt and water secretion into the ASL in the face of mucin hypersecretion, causing ASL/mucus dehydration and reduced mucus clearance, thus leading to impaired innate defense (14,17). However, as with many aspects of tobacco exposure, the cell biology underlying CFTR's inhibition following tobacco exposure is likely to be complex, and the underlying mechanisms are currently unknown.…”
mentioning
confidence: 99%
“…CS is highly oxidizing, which decreases CFTR gene expression, and CS exposure also causes CFTR clearance from the plasma membrane into aggresome-like compartments (14,16). Both of these effects result in a functional decrease in CFTR activity in the plasma membrane, which reduces salt and water secretion into the ASL in the face of mucin hypersecretion, causing ASL/mucus dehydration and reduced mucus clearance, thus leading to impaired innate defense (14,17). However, as with many aspects of tobacco exposure, the cell biology underlying CFTR's inhibition following tobacco exposure is likely to be complex, and the underlying mechanisms are currently unknown.…”
mentioning
confidence: 99%
“…The prolonged decrease in galactose content in dogs exposed was interpreted as a change in the nature of the mucus. In humans, we previously demonstrated an almost identical pattern regarding a fall in mucus rigidity with an eventual return to normal values (4,7). It is tempting to assume that a similar biochemical change in mucus composition might have happened in these subjects as well.…”
Section: Discussionmentioning
confidence: 74%
“…any studies have shown that smoking leads to abnormalities in mucus clearance, both in humans (1)(2)(3)(4) and in animals (5). We have demonstrated that canine mucus rheology is altered by cigarette smoke exposure, initially in a way that predictive equations suggest would increase mucociliary transportability (6).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…We found, for example, that respiratory mucus from asymptomatic smokers is better hydrated and more easily cleared by mucociliary action than mucus from nonsmokers [60]. However, this apparent "advantage" to smoking disappears with continued exposure, over the course of 20-40 pack-years, and abnormalities in the elastic recoil of mucus predictive of poor cough clearance eventually develop [61].…”
Section: Large Animal Models For Mucus Hypersecretionmentioning
confidence: 73%